Pengaruh Komposisi Jenis Kelamin Pada Dinamika Pelaksanaan Bimbingan Kelompok - Rosyidah, Titin; Darminto, Eko; Hariastuti, Retno Tri (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
The composition of the sex-based group is operationally defined as three groups in the guidance group which are formed homogeneously and heterogeneously based on gender, namely: the male homogeneous group, the female homogeneous group, and the heterogeneous sex group. This study aims to direct the influence of gender-based group composition in group guidance groups on group dynamics. The research was conducted through a quasi-experimental approach with a nonequivalent control group design. The research subjects were 30 randomly selected from students at SMP Negeri 1 Pungging. The One-Way ANOVA test analysis results showed a p-value (sig. 0.000), so it was known that p <0.05. These calculations prove that gender-based group composition in the guidance group has a significant positive effect on group dynamics. The implication of this finding is that guidance groups for junior high school students will be effective if they are made up homogeneously based on gender, especially the female sex.